Comparing the T scores from bone sonometer measurements in Hispanic and non-Hispanic white women - Droege M; Marsh WA; Alvarez GN; Hunter TS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Ethnicity is an important risk factor for the development of osteoporosis. Non-Hispanic white or Asian women are commonly considered at higher risk than other ethnicities. Hispanics in the U.S. are of Mexican, Caribbean, Central American, or South American descent. Conclusive data on the relative risk of osteoporosis in Hispanic women based upon heritage within the Hispanic population are not available. Objective: To investigate whether Hispanic white women are at a significantly lower risk than non-Hispanic whites for the development of osteoporosis. Methods: Cross-sectional study. Setting: Community health screenings. Participants: Hispanic and non-Hispanic white women. Intervention: Bone density measurements of the non-dominant heel. Descriptive statistics and inferential statistics including regression analyses were performed using SPSS 14.0. Main Outcomes Measure: T scores. Results: Overall, measurements were obtained from 352 women (209 Hispanic & 143 non-Hispanic white) ranging in age from 55-97 years old. The mean T score obtained for Hispanic women was -1.194 and -1.280 for non-Hispanic white women. The correlation between the obtained T score and age was negative (r = -0.36, p<0.01), reflecting bone loss with increasing age. Regression analysis using age and ethnicity showed that ethnicity was a non-significant contributor to the best-fit regression line (t=0.60, p=0.55). Conclusion: This study indicates that Hispanic white women may be at comparable risk of developing osteoporosis as non-Hispanic white women.